REKONTRUKSI MODEL INTEGRASI UKM DAN LKM KE DALAM CITA-CITA DESA MELALUI BUMDesa DI KABUPATEN BANYUWANGI - Emi Hidayati; Nurul Fatimah (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2022)
The management of microfinance institutions in the village has not been directed with certainty. The management of micro-enterprises and units of microfinance institutions aims to be integrated into the management of BUMDes. This requires a deeper study to find out the consolidation model and its management. This study used qualitative research methods. The selection of this qualitative method is based on the consideration of the need to deepen the meaning of a phenomenon. Based on the study and the results of research and discussion, it can be concluded: 1) With this microfinance institution, small and medium enterprises can find solutions that have been one of the problems; 2) establishment and management of Village Owned Enterprises (BUMDes) by integrating the existence of Micro Finance Institutions (LKM) into business units, is actually very strategic for efforts to maximize the role of developing rural micro productive economic enterprises; 3) The reasons for objecting to consolidation or integration are still about sectoral egos, all parties do not feel it is important to position the village as a place to live, do not believe that the village can play a role in building self-reliance and prospering the community.